Aminoferrocene-based prodrugs and their effects on human normal and cancer cells as well as bacterial cells - Marzenell, Paul; Hagen, Helen; Sellner, Leopold; Zenz, Thorsten; Grinyte, Ruta; Pavlov, Valeri; Daum, Steffen; Mokhir, Andriy (Journal of Medicinal Chemistry, 2013)
Aminoferrocene-based prodrugs are activated under cancer-specific conditions (high concentration of reactive oxygen species, ROS) with the formation of glutathione scavengers (p-quinone methide) and ROS-generating iron complexes. Herein, we explored three structural modifications of these prodrugs in an attempt to improve their properties: (a) the attachment of a -COOH function to the ferrocene fragment leads to the improvement of water solubility and reactivity in vitro but also decreases cell-membrane permeability and biological activity, (b) the alkylation of the N-benzyl residue does not show any significant affect, and (c) the attachment of the second arylboronic acid fragment improves the toxicity (IC) of the prodrugs toward human promyelocytic leukemia cells (HL-60) from 52 to 12 μM. Finally, we demonstrated that the prodrugs are active against primary chronic lymphocytic leukemia (CLL) cells, with the best compounds exhibiting an IC value of 1.5 μM. The most active compounds were found to not affect mononuclear cells and representative bacterial cells. © 2013 American Chemical Society.

An Endoplasmic Reticulum Specific Pro-amplifier of Reactive Oxygen Species in Cancer Cells - Xu, Honggui; Schikora, Margot; Sisa, Miroslav; Daum, Steffen; Klemt, Insa; Janko, Christina; Alexiou, Christoph; Bila, Galyna; Bilyy, Rostyslav; Gong, Wenjie; Schmitt, Michael; Sellner, Leopold; et al. (Angewandte Chemie International Edition, 2021)
The folding and export of proteins and hydrolysis of unfolded proteins are disbalanced in the endoplasmic reticulum (ER) of cancer cells, leading to so-called ER stress. Agents further augmenting this effect are used as anticancer drugs including clinically approved proteasome inhibitors bortezomib and carfilzomib. However, these drugs can affect normal cells, which also rely strongly on ER functions, leading, for example, to accumulation of reactive oxygen species (ROS). To address this problem, we have developed ER-targeted prodrugs activated only in cancer cells in the presence of elevated ROS amounts. These compounds are conjugates of cholic acid with N-alkylaminoferrocene-based prodrugs. We confirmed their accumulation in the ER of cancer cells, their anticancer efficacy, and cancer cell specificity. These prodrugs induce ER stress, attenuate mitochondrial membrane potential, and generate mitochondrial ROS leading to cell death via necrosis. We also demonstrated that the new prodrugs are activated in vivo in Nemeth-Kellner lymphoma (NK/Ly) murine model.
CRIS-Team WoS Importer:2021-04-16

Evaluation of N-alkylaminoferrocenes for in-vivo imaging of reactive oxygen species activity using PET and optical imaging - Toms, Johannes; Maschauer, Simone; Daum, Steffen; Reshetnikov, Viktor; Mokhir, Andriy; Prante, Olaf (JOURNAL OF LABELLED COMPOUNDS & RADIOPHARMACEUTICALS, 2019)
CRIS-Team WoS Importer:2019-06-18

Hybrids of a 9-anthracenyl moiety and fluorescein as chemodosimeters for the detection of singlet oxygen in live cells - Chercheja, Serghei; Daum, Steffen; Xu, Honggui; Beierlein, Frank; Mokhir, Andriy (Organic & Biomolecular Chemistry, 2019)
Singlet oxygen (1O2) plays an important role in human innate immune response, plant physiology and anticancer photodynamic therapy (PDT). Therefore, its monitoring by convenient and sensitive methods (e.g. by detecting a fluorescence signal) by using non-toxic reagents would be advantageous. Known fluorogenic 1O2-chemodosimeters can potentially consume reducing agents in cells leading to the generation of toxic side products that limit their applications. In this paper we report on a series of 9-anthracenyl-fluorescein hybrids, which do not require any reducing agents for their reaction with 1O2. The selected compound 8d at a very low concentration of 100 nM is able to detect 1O2 in live human promyelocytic leukemia HL-60 cells with over 35-fold fluorescence signal enhancement within only 20 min assay time. This chemodosimeter is not toxic to HL-60 cells at concentrations ≤1 μM (higher concentrations were not tested) even at long incubation times ≤48 h.
CRIS-Team Scopus Importer:2019-12-10

Identification of Boronic Acid Derivatives as an Active Form of N-Alkylaminoferrocene-Based Anticancer Prodrugs and Their Radiolabeling with 18F - Daum, Steffen; Toms, Johannes; Reshetnikov, Viktor; Özkan, Hülya; Hampel, Frank; Maschauer, Simone; Hakimioun, Amir Hossein; Beierlein, Frank; Sellner, Leopold; Schmitt, Michael; Prante, Olaf; Mokhir, Andriy (Bioconjugate Chemistry, 2019)
N-Alkylaminoferrocene (NAAF)-based prodrugs are activated in the presence of elevated amounts of reactive oxygen species (ROS), which corresponds to cancer specific conditions, with formation of NAAF and p-quinone methide. Both products act synergistically by increasing oxidative stress in cancer cells that causes their death. Though it has already been demonstrated that the best prodrugs of this type retain their antitumor activity in vivo, the effects were found to be substantially weaker than those observed in cell cultures. Moreover, the mechanistic studies of these compounds in vivo are missing. For clarification of these important questions, labeling of the prodrugs with radioactive moieties would be necessary. In this paper, we first observed that the representative NAAF-based prodrugs are hydrolyzed in dilute aqueous solutions to the corresponding arylboronic acids. We confirmed that these products are responsible for ROS amplification and anticancer properties of the parent prodrugs. Next, we developed the efficient synthetic protocol for radiolabeling the hydrolyzed NAAF-based prodrugs by [18F]fluoroglucosylation under the conditions of the copper(I)-catalyzed azide–alkyne 1,3-dipolar cycloaddition and used this protocol to prepare one representative hydrolyzed NAAF-based prodrug radiolabeled with 18F. Finally, we studied the stability of the 18F-labeled compound in human serum in vitro and in rat blood in vivo and obtained preliminary data on its biodistribution in vivo in mice carrying pancreatic (AR42J) and prostate (PC3) tumors by applying PET imaging studies. The compound described in this paper will help to understand in vivo effects (e.g., pharmacokinetics, accumulation in organs, the nature of side effects) of these prodrugs that will strongly contribute to their advancement to clinical trial

Intracellular amplifiers of reactive oxygen species affecting mitochondria as radiosensitizers - Xu, Honggui; Reshetnikov, Viktor; Wondrak, Marit; Eckhardt, Lisa; Kunz-Schughart, Leoni A.; Janko, Christina; Tietze, Rainer; Alexiou, Christoph; Borchardt, Hannes; Aigner, Achim; Gong, Wenjie; Schmitt, Michael; et al. (Cancers, 2022)
Radiotherapy (RT) efficacy can be improved by using radiosensitizers, i.e., drugs enhancing the effect of ionizing radiation (IR). One of the side effects of RT includes damage of normal tissue in close proximity to the treated tumor. This problem can be solved by applying cancer specific radiosensitizers. N-Alkylaminoferrocene-based (NAAF) prodrugs produce reactive oxygen species (ROS) in cancer cells, but not in normal cells. Therefore, they can potentially act as cancer specific radiosensitizers. However, early NAAF prodrugs did not exhibit this property. Since functional mitochondria are important for RT resistance, we assumed that NAAF prodrugs affecting mitochondria in parallel with increasing intracellular ROS can potentially exhibit synergy with RT. We applied sequential Cu+-catalyzed alkyne-azide cycloadditions (CuAAC) to obtain a series of NAAF derivatives with the goal of improving anticancer efficacies over already existing com-pounds. One of the obtained prodrugs (2c) exhibited high anticancer activity with IC50 values in the range of 5–7.1 µM in human ovarian carcinoma, Burkitt’s lymphoma, pancreatic carcinoma and T-cell leukemia cells retained moderate water solubility and showed cancer specificity. 2c strongly affects mitochondria of cancer cells, leading to the amplification of mitochondrial and total ROS production and thus causing cell death via necrosis and apoptosis. We observed that 2c acts as a radiosensitizer in human head and neck squamous carcinoma cells. This is the first demonstration of a synergy between the radiotherapy and NAAF-based ROS amplifiers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Cancer; Mitochondrion; N-alkylaminoferrocene; Prodrug; Radiotherapy; Reactive oxygen species

Lysosome-targeting amplifiers of reactive oxygen species as anticancer prodrugs - Daum, Steffen; Reshetnikov, Viktor; Sisa, Miroslav; Dumych, Tetyana; Lootsik, Maxim D.; Bilyy, Rostyslav; Bila, Evgenia; Janko, Christina; Alexiou, Christoph; Herrmann, Martin; Sellner, Leopold; Mokhir, Andriy (Angewandte Chemie-International Edition, 2017)
Cancer cells produce elevated amounts of reactive oxygen species that has been used to design cancer specific prodrugs. Their activation relies on at least a bimolecular process, where a prodrug reacts with ROS. However, at low µM concentrations of the prodrugs and ROS the activation is usually inefficient. Herein we suggested and validated a potentially general approach for solving this intrinsic problem of ROS-dependent prodrugs. In particular, known 4-(N-ferrocenyl-N-benzylaminocarbonyloxymethyl)phenylboronic acid pinacol ester was converted to its lysosome specific analogue. Since lysosomes contain the higher concentration of active ROS than cytoplasm, activation of the latter prodrug was facilitated with respect to the parent compound. In particular, it was found to exhibit high anticancer activity in a variety of cancer cell lines (IC50 3.5-7.2 µM) and in vivo (40 mg/kg, NK/Ly murine model), but remained weakly toxic towards non-malignant cells (IC50 15-30 µM).
EVALuna2:13450

N-Alkylaminoferrocene-Based Prodrugs Targeting Mitochondria of Cancer Cells - Reshetnikov, Viktor; Özkan, Hülya; Daum, Steffen; Janko, Christina; Alexiou, Christoph; Sauer, Caroline; Heinrich, Markus; Mokhir, Andriy (Molecules, 2020)
Intracellular concentration of reactive oxygen species (e.g., H2O2) in cancer cells is elevated over 10-fold as compared to normal cells. This feature has been used by us and several other research groups to design cancer specific prodrugs, for example, N-alkylaminoferrocene (NAAF)-based prodrugs. Further improvement of the efficacy of these prodrugs can be achieved by their targeting to intracellular organelles containing elevated reactive oxygen species (ROS) amounts. For example, we have previously demonstrated that lysosome-targeted NAAF-prodrugs exhibit higher anticancer activity in cell cultures, in primary cells and in vivo (Angew. Chem. Int. Ed. 2017, 56, 15545). Mitochondrion is an organelle, where electrons can leak from the respiratory chain. These electrons can combine with O2, generating O2-• that is followed by dismutation with the formation of H2O2. Thus, ROS can be generated in excess in mitochondria and targeting of ROS-sensitive prodrugs to these organelles could be a sensible possibility for enhancing their efficacy. We have previously reported on NAAF-prodrugs, which after their activation in cells, are accumulated in mitochondria (Angew. Chem. Int. Ed. 2018, 57, 11943). Now we prepared two hybrid NAAF-prodrugs directly accumulated in mitochondria and activated in these organelles. We studied their anticancer activity and mode of action. Based on these data, we concluded that ROS produced by mitochondria is not available in sufficient quantities for activation of the ROS-responsive prodrugs. The reason for this can be efficient scavenging of ROS by antioxidants. Our data are important for the understanding of the mechanism of action of ROS-activatable prodrugs and will facilitate their further development.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cancer; mitochondrion; N-alkylaminoferrocene; prodrug; reactive oxygen species

ROS-Responsive N-Alkylaminoferrocenes for Cancer-Cell-Specific Targeting of Mitochondria - Reshetnikov, Viktor; Daum, Steffen; Janko, Christina; Karawacka, Weronika; Tietze, Rainer; Alexiou, Christoph; Paryzhak, Solomiya; Dumych, Tetiana; Bilyy, Rostyslav; Tripal, Philipp; Schmid, Benjamin; Palmisano, Ralf; et al. (Angewandte Chemie International Edition, 2018)
Mitochondrial membrane potential is more negative in cancer cells than in normal cells, allowing cancer targeting by delocalized lipophilic cations (DLCs). However, as the difference is rather small, these drugs affect also normal cells. Now a concept of pro-DLCs is proposed based on an N-alkylaminoferrocene structure. These prodrugs are activated by the reaction with reactive oxygen species (ROS) forming ferrocenium-based DLCs. Since ROS are overproduced in cancer, the high-efficiency cancer-cell-specific targeting of mitochondria could be achieved as demonstrated by fluorescence microscopy in combination with two fluorogenic pro-DLCs in vitro and in vivo. We prepared a conjugate of another pro-DLC with a clinically approved drug carboplatin and confirmed that its accumulation in mitochondria was higher than that of the free drug. This was reflected in the substantially higher anticancer effect of the conjugate.
EVALuna2:35451

Tuning the structure of aminoferrocene-based anticancer prodrugs to prevent their aggregation in aqueous solution - Daum, Steffen; Babiy, Svetlana; Konovalova, Helen; Hofer, Walter; Shtemenko, Alexander; Shtemenko, Natalia; Janko, Christina; Alexiou, Christoph; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2018)
Aminoferrocene-based prodrugs are activated in cancer cells by reactive oxygen species (ROS). They were shown to exhibit high cytotoxicity towards a variety of cancer cell lines and primary cancer cells, but remain not toxic towards non-malignant cells. However, these prodrugs have rather high lipophilicity leading to relatively low water solubility. In particular, an n-octanol/water partition coefficient for the best aminoferrocene-based pro drug (2) was found to be 4.51 +/- 0.03. Though the approaches for decreasing lipophilicity are straightforward and include the addition of polar residues to the drug structure, these modifications also lead to dramatic decrease of cell permeability and, correspondingly, lower the activity of the drug. Therefore, a delicate balance of polar and unpolar groups should be found to reduce lipophilicity without compromising the useful drug properties. In this study we optimized an N-alkyl substituent, which is a key element responsible for the stabilization of the aminoferrocene drug released in cancer cells from prodrug 2. We found that an N-propargyl residue is an optimal replacement for the N-benzyl fragment. In particular, such a substitution (prodrug 7a) leads to reduction of prodrug lipophilicity down to logP = 3.78 +/- 0.05, improvement of its water solubility, decrease of its propensity towards aggregation and dramatic increase of its ROS-generating properties. Finally, we demonstrated that the optimized prodrug strongly suppresses growth of Guerin's carcinoma (T8) in vivo at the dose of 30 mg/kg.
EVALuna2:213359